2016
DOI: 10.1080/19490976.2016.1256524
|View full text |Cite
|
Sign up to set email alerts
|

Support for the microgenderome invites enquiry into sex differences

Abstract: The microgenderome defines the interaction between microbiota, sex hormones and the immune system. Our recent research inferred support for the microgenderome by showing sex differences in microbiota-symptom associations in a clinical sample of patients with myalgic encephalomyelitis / chronic fatigue syndrome (ME/CFS). This addendum expands upon the sex-specific pattern of associations that were observed. Interpretations are hypothesized in relation to genera versus species-level analyses and D-lactate theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…It is becoming evident that the sex hormones have an impact on microbioma and consequently on immune responses [15]. On the other hand, gut microbiota can modify the systemic levels of testosterone via 17β reduction of androgen but still lack adequate information on the mechanism by which sex hormones derived by microbiome impact on the host immune response [19,20]. Immune cell populations vary between the sexes: females from birth have a higher proportion of CD4+ T lymphocytes than male, CD4+ and CD8+ T cells decline with age in both sexes though compared to men, and aged women show lower memory Tregs and NK cells.…”
Section: Hormones Chromosomes Immunity and Allergymentioning
confidence: 99%
See 1 more Smart Citation
“…It is becoming evident that the sex hormones have an impact on microbioma and consequently on immune responses [15]. On the other hand, gut microbiota can modify the systemic levels of testosterone via 17β reduction of androgen but still lack adequate information on the mechanism by which sex hormones derived by microbiome impact on the host immune response [19,20]. Immune cell populations vary between the sexes: females from birth have a higher proportion of CD4+ T lymphocytes than male, CD4+ and CD8+ T cells decline with age in both sexes though compared to men, and aged women show lower memory Tregs and NK cells.…”
Section: Hormones Chromosomes Immunity and Allergymentioning
confidence: 99%
“…information on the mechanism by which sex hormones derived by microbiome impact on the host immune response [19,20]. Immune cell populations vary between the sexes: females from birth have a higher proportion of CD4+ T lymphocytes than male, CD4+ and CD8+ T cells decline with age in both sexes though compared to men, and aged women show lower memory Tregs and NK cells.…”
Section: Hormones Chromosomes Immunity and Allergymentioning
confidence: 99%
“…Using gonadectomized and hormone-treated mice clearly revealed hormonal effects on the GM composition [ 172 ]. In humans, sex-specific interactions between Firmicutes and neurological, immune and mood symptoms of myalgic encephalomyelitis/chronic fatigue syndrome have been reported [ 173 ], but we are just beginning to appreciate the links between human microbiome composition and hormonal phenotypes. Twin studies have revealed that the once similar microbial composition of opposite-sex twins becomes distinctly different after puberty when compared to that of same-sex twins which remains compositionally similar [ 57 ].…”
Section: Gut Microbiota and Host Genetics: An Intimate Evolutionary-smentioning
confidence: 99%
“…Gastrointestinal disturbances are well documented in CFS/ME (Logan et al, ; Sheedy et al, ; Fremont et al, ; Giloteaux et al, ; Navaneetharaja et al, ; Wallis et al, ). However, the association of CFS/ME with an altered microbiota‐gut‐brain axis and faecal microbiota transplantation remains unclear.…”
Section: Faecal Microbiota Transplantationmentioning
confidence: 99%